DAMPAK POSITIF AKTIVITAS WISATA SPIRITUAL MELUKAT DI PURA PABERSIHAN SURANADI BAGI KESEJAHTERAAN INDIVIDU WISATAWAN - I Made Sugita Darmateja (Paryaṭaka Jurnal Pariwisata Budaya dan Keagamaan, 2026)
This study explores the positive impacts of the Melukat spiritual tourism activity at Pura Tirtha Pabersihan Suranadi on tourists’ individual wellbeing, particularly in psychological, emotional, and spiritual dimensions. Grounded in contemporary discourse on spiritual tourism that highlights holistic experience and inner transformation, this article aims to explain how the Melukat ritual functions as a medium for mental restoration as well as life meaning-making for modern tourists. A qualitative descriptive design was employed, using in-depth interviews with 15 repeat visitors selected through purposive sampling, complemented by participant observation and on-site documentation. Data were analyzed through systematic stages of reduction, display, and conclusion drawing based on inductively emerging themes. The findings show that Melukat is capable to shape three key self-wellbeing benefits for tourists: it reduces stress and anxiety, bringing a sense of relief, calm, and a more optimistic outlook on life; it enhances emotional balance by improving the ability to manage negative emotions, strengthening inner resilience, and supporting clearer decision-making; and it elevates spiritual awareness through deepened faith, self-reflection, and congruence between tourists’ inner values and the sacred atmosphere of the destination.Theoretically, this study enriches spiritual tourism scholarship by positioning Melukat as a local, holistic practice that supports harmony of body, mind, and soul. Practically, the results are crucial for destination management to preserve sacred authenticity while optimizing wellbeing-oriented narratives in the development of sustainable spiritual tourism. Keywords : Melukat, spiritual tourism, psychological wellbeing, emotional balance, spiritual awareness